(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: It is generally acknowledged that one of the most significant issues facing modern human are those with broad activity spectra that render all or most medicines in a particular treatment category ineffective. Objective: The goal of this study is to evaluate the microbiological quality of raw meat, specifically focusing on the frequency of Extended-Spectrum Beta-Lactamases (ESBL) production among Enterobacteriaceae, and to assess the antibiotic susceptibility of these isolates in vitro as well as to conduct a molecular characterization of ESBL to better understand the genetic mechanisms behind their production. Methodology: This comparative cross-sectional study was conducted in neighborhood marketplaces of Dhaka, including Bashundhara, Azimpur, and Dhanmondi Bazar, from November 2022 to August 2023. A total of 40 beef and mutton samples were collected directly from slaughterhouses and transported to the NSU laboratory in sterile Ziploc bags without freezing. For pure culture, Mac Conkey agar plates were utilized after sample collection. Muller-Hinton agar media (MHA) was used for antibiotic susceptibility testing after completion of organism detection test on Eosin-methylene blue (EMB) agar media. DNA was extracted using the hot boiling method. The purity of the DNA was assessed to ensure its quality. Gel electrophoresis was then performed to verify DNA integrity. Finally, PCR was conducted for genetic confirmation of specific sequences. Results: Among 40 samples, 95% of the bacteria discovered belonged to the Enterobacteriaceae family. Five (or 25%) of the beef samples showed resistance against the combination of Ceftazidime (CAZ) and Amoxicillin-Clavulanic acid (AMC). About the mutton, 20 (100%) cases were found resistant to CAZ+AMC (100%), and 12 instances were resistant to CTX (Cefotaxime) +AMC (60%). Several strains (17.5%) in our investigations demonstrated phenotypic positive for producing the ESBL enzyme. Of 40 dietary samples, 35% of the strains that create ESBL are identified in beef and mutton, respectively, with 30% and 5% 0f theses strains producing ESBL. In this study, the focus was on two specific gene types, namely the VIM and DHA genes. The genotype known as blaDHA (Variation of the dihydrofolate reductase gene) was identified as the causative factor in 2.5% of all cases, while the genotype referred to as blaVIM (Verona -Integron encoded- Metallo-beta-lactamases) was responsible for 2.5% of the cases of total 40 strains. Conclusion: Antibiotic resistance is an important health issue due to the potential pathogenicity. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):26-34